Kepastian Hukum Dalam Kepemilikan Tanah - Putri, Alexandra Vandela; Boantua M, Yuris Utrecht; Purwa, Rumi Alghozali; Naomi M. G, Juniartha Gladys; Tarina, Dwi Desi Yayi (Media Hukum Indonesia (MHI), 2024)
Legal certainty over land ownership is very important to create justice and stability in land management in Indonesia. This research aims to understand the concept of legal certainty in land ownership through literature review. The method used is a literature study, which collects and analyzes various legal sources, such as laws, expert opinions, and previous research. The results show that legal certainty of land ownership depends on clear rules, an effective land registration process, and consistent law enforcement. However, problems such as land conflicts, overlapping certificates, and weak land administration often become obstacles. This research suggests improved rules, the use of technology in land administration, and legal education to the community to strengthen the protection of land ownership.